Pengaruh Konservatisme Akuntansi, Tata Kelola Perusahaan Dan Struktur Kepemilikan Terhadap Efisiensi Investasi - Fitriyah, Lailatul; Suwarno, Suwarno (Universitas Muhammadiyah Gresik, 2024)
This research aims to examine the effect of accounting conservatism, corporate governance and ownership structure on investment efficiency in financial companies listed on the Indonesia Stock Exchange during the period 2017-2019. The sample of this study was selected by using purposive sampling and obtained as many as 114 data with 38 companies per year. The hypothesis testing in this study using multiple linear regression model. Partially, the results indicates that managerial ownership has an effect on investment efficiency. While the other four variables, namely accounting conservatism, independent commissioners, audit committees, and institutional ownership have no effect on investment efficiency.